Improvement of Accounting Teacher Competencies Through E-Book Creation Training as An Alternative Teaching Material (Universitas Negeri Semarang, 2022)
Teacher competence in a learning process is a crucial ingredient that must be continuously improved. Changes in learning implementation strategies during the Covid-19 pandemic provide opportunities and challenges for teachers, especially regarding learning to provide the best service to students. The use of e-books by flipbook applications is considered an alternative to help the learning process. This community service activity aims to improve teacher competence in developing digital media by using flipbook applications as alternative media during online learning. After making an e-book with the flipbook application, it is hoped that the teacher will be more helpful in providing material to students. The activity was carried out through a zoom cloud meeting involving 42 teachers of SMK Negeri 1 Boyolali. The method used in this activity is the importance of managing online learning, training in making e-books using flipbook applications, assisting in making e-books, and evaluating activities. The result of this activity is that teachers can understand digital media's importance and practice making digital media e-books using flipbook applications. Kompetensi guru dalam sebuah proses pembelajaran menjadi hal pokok yang harus selalu ditingkatkan. Perubahan strategi pelaksanaan pembelajaran pada masa Pandemi Covid-19 memberikan peluang dan sekaligus tantangan bagi guru khususnya terkait dengan pelaksanaan pembelajaran untuk memberikan pelayanan terbaik kepada siswa. Pemanfaatan media digital e-book dengan memanfaatkan aplikasi flipbook dirasakan menjadi sebuah alternatif untuk membantu kelancaran proses pembelajaran. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kompetensi guru dalam mengembangkan media digital dengan menggunakan aplikasi flipbook sebagai media alternatif selama pembelajaran online. Kegiatan dilaksanakan melalui zoom cloud meeting dengan melibatkan 42 guru SMK Negeri 1 Boyolali. Metode yang digunakan dalam kegiatan ini adalah sosialisasi pentingnya mengelola pembelajaran online, pelatihan pembuatan e-book dengan memanfaatkan aplikasi flipbook, pendampingan pembuatan e-book, dan evaluasi kegiatan. Hasil dari kegiatan ini adalah guru dapat memahami pentingnya media digital dan guru dapat mempraktikkan cara membuat media digital e-book dengan memanfaatkan aplikasi flipbook.